Monitoring Educational Performance in the Caribbean - World Bank (Washington, DC, 2013)
The study seeks to define a set of operationally relevant education indicators, to be used by countries in the Caribbean region, to provide a database of comparable education indicators in Caribbean countries where data is available, namely Belize, Dominica, Dominican Republic, Grenada, Guyana, Jamaica, St. Kitts and Nevis, St. Lucia, St. Vincent and the Grenadines, and Trinidad and Tobago, and, to propose methods on how the common set of indicators can be used for analyses of the education sectors. Following the introduction under Section I, which addresses the current deficiencies in the Caribbean education system, Section II defines operationally relevant education indicators in the areas of coverage, efficiency, and quality. In these areas, enrollment ratios should be complemented with grade-specific indicators, efficiency complemented with a cost-effectiveness analysis, and, quality with a variety of standardized tests. Monitoring of education indicators in the Caribbean Region, is then reviewed in Section III, stipulating that despite a traditional limited availability of education statistics, and indicators, there has recently been substantial efforts - both at national, and regional levels - to improve data collection. The new indicator database on ten Caribbean Countries describes, and analyzes updated indicators so as to balance diagnostics of the education sectors relevant to policy decisions, and, ensures comparability to all countries, based on country syntheses, and cross-country comparison. Finally, Section IV provides policy recommendations, that include the need to measure the coverage, and efficiency of the entire education cycle; to produce, and use grade-specific indicators, such as the completion, and survival rates; to harmonize education statistics and indicators to improve reporting and monitoring in a systematic way; and, to participate in international exams to make meaningful comparison of learning outcomes, and produce qualitative indicators.